Mechanics of materials characterization of lead-free solders - Xiong, Bingshou (2008)
Lead-free solders will replace tin-lead solders in electronic products due to European Union laws to restrict the use of toxic materials like lead (Pb) in electronic equipment by July 1st, 2006. Legislation to ban the use of lead (Pb) is forcing the electronic industry to use lead-free solders. Solder interconnections serve as electrical connections and also as the mechanical support to hold the IC component in position on the printed circuit board (PCB). It is important to characterize the mechanical properties of lead-free solders. NEMI (National Electronic Manufacturing Initiative) recommends Sn-3.9Ag-0.6Cu(±0.2%) for reflow soldering process and Sn-0.7Cu solder alloy for wave soldering. The scope of this study includes the two NEMI recommended Pb-free solder alloys, namely Sn-3.8Ag-0.7Cu and Sn-0.7Cu. A mechanics of materials characterization of the elastic-plastic-creep properties and low cycle fatigue behavior is reported. A new visco-plastic constitutive model and fatigue model is presented and used to model the thermal fatigue behavior of a Micro-BGA assembly.